A terceirização do jogador de futebol - Lima, Renato Pinheiro de (2020)
The Master of Laws dissertation here presented consists in the outcomes of a research on the possibility of outsourcing the professional sports athlete’s labour contract, considering the soccer player as a background example. The soccer athlete was chosen due to the more rigid regulation of his respective contract in Brazilian Law 9,615 in relation to all other professional athletes. In this sense, when the most rigid rules are analysed it is possible, if the proposed thesis is validated, to conclude by deduction that all other cases allow outsourcing. Then, it was adopted as a research question the doubt on the possibility of outsourcing not the contract, but the services provided by professional athletes, and as answer, the affirmative one. The research was funded on two methodological strategies. The first, predominantly descriptive, with emphasis on the majority interpretation by doctrine and the Brazilian courts, allowed to characterize both the professional employment contract of the soccer player considering the Law 9,615 (second chapter), and the outsourcing as labour institute (third chapter), considering the Brazilian Law 6,019. The second, predominantly dialectical, allowed (fourth chapter) the understanding of the contrary (the argument for the precariousness) and favourable (the argument for the globalization) views about the possibility of outsourcing any activities, to conclude by the validity of the launched thesis (the argument for the possibility). At the conclusion topic, the consolidated answer is presented, as well as identified the need for more in-depth studies and systematization, in order to create more efficient mechanisms not only for controlling and correcting, but also for managing labour market strategies, both in public and private sectors